COMPARATIVE ANALYSIS OF CRITICAL SPEECH IN TRANSLATION - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
Critical discourse analysis is the most important part that a translator cannot miss. A translator must be able to deal with any text and deepen the context inherent in the sentence to be analyzed. Even after the Van Dijk discourse, the text is of exceptional contextual analysis. From the perspective of language according to Eriyanto: 1) language is a bridge between people and objects outside themselves, 2) subject is a central factor in discourse activity and social relations, and 3) language is a formative representation of a particular theme, purpose, and strategy therein. Critical Discourse Analysis (CDA) is a cutting-edge approach to extracting and deconstructing a specific purpose and critically analyzing discourse and the multiple interests that shape it.